LITERASI MEDIA DIGITAL BAGI GURU PAUD GUGUS KENANGA DI KECAMATAN DUKUHSETI KABUPATEN PATI - Raodah Saidillah; Ali Subhan (As-Sidanah, 2020)
This outreach program is Digital Media Literacy Training for early childhood education (PAUD) Teachers of Kenanga Group in Dukuhseti district, Pati regency. This digital media literacy training activity aims to provide knowledge and insight into early childhood education (PAUD) Teachers to take advantage of digital-based media both in learning and administration. This outreach program was held for two days on Thursday-Friday, 29-30 August 2019 at TK Tunas Bangsa. The material presented includes; the urgency and function of digital media for learning and administration, typing using Microsoft Word, presenting with PowerPoint, scanning documents using a device, and using the WhatsApp application by computer or laptop. It is designed in the form of training using three methods. They are lecture method, demonstration method, and direct practice method. The results indicate that this program significantly increases in knowledge, understanding, expertise and, skills of the participants. It can be seen from the results of the pretest and posttest that have been implemented. Participants were also very satisfied with the dedication activities that had been carried out because the material presented was fit their needs and the methods used were also appropriate. From all the evaluation results in the form of pretest, posttest and feedback from the participants, it was concluded that this outreach program has achieved the goal they are the participants understand and can apply digital media for learning and administration.